Canva Application-Based E-Komikkuis in Natural and Social Sciences (IPAS) learning to Improve Science Literacy - I Putu Wahyu Prasetyawan; Desak Putu Parmiti; I Wayan Sujana (International Journal of Language and Literature, 2026)
This research is motivated by the low scientific literacy of fifth-grade students in science learning, which is characterized by difficulty understanding concepts and a lack of learning engagement. This study aims to develop an E-Komikkuis based on the Canva application as an interesting, interactive learning medium that can improve students' scientific literacy. The development model used is ADDIE with 28 fifth-grade students in an elementary school as research subjects. Data collection methods and instruments used questionnaires and tests. Data were analyzed using quantitative descriptive and inferential techniques to assess the feasibility of the media and the effectiveness of its use. The results showed that E-Komikkuis was considered very feasible by media experts and material experts, and received positive responses from students. The use of this media was proven to improve students' conceptual understanding and scientific literacy skills significantly. This study implies that visual-interactive media such as E-Komikkuis can be an effective alternative in science learning and encourages teachers to be more creative in developing digital media that is interesting and relevant to students' needs.